Methodology for the development of national intellectual property strategies (WIPO publication, 2020)
"The prime audience for this guide is the national project team that has been charged with the responsibility of developing a national IP strategy. A secondary audience is any steering committee that has been established to oversee the team and any other management arrangements put in place to oversee the work of the national project team. The guide can also be used by any interested parties to gain a better insight into or understanding of how national IP strategies could be formulated and implemented based on the experiences of WIPO in working closely with the national authorities and stakeholder groups from member states in different regions of the world."--Background, page 6 "La audiencia principal de esta guía es el equipo de proyecto nacional al que se ha encargado la responsabilidad de desarrollar una estrategia nacional de PI. Una audiencia secundaria es cualquier comité directivo que se haya establecido para supervisar al equipo y cualquier otro arreglo de gestión establecido para supervisar el trabajo del equipo nacional del proyecto. La guía también puede ser utilizada por cualquier parte interesada para obtener una mejor perspectiva o comprensión de cómo se pueden formular y aplicar estrategias nacionales de PI sobre la base de las experiencias de la OMPI en su estrecha colaboración con las autoridades nacionales. y grupos de partes interesadas de estados miembros en diferentes regiones del mundo".--Antecedentes, página 6